6-(6-methyl-1,2,4,5-tetrazine-3-yl)-2,2′-bipyridine: a N-donor ligand for the separation of lanthanides(III) and actinides(III) - Greif, Gerlinde; Sauerwein, Fynn S.; Weßling, Patrik; Duckworth, Tamara M.; Patzschke, Michael; Gericke, Robert; Sittel, Thomas; März, Juliane; Wilden, Andreas; Modolo, Giuseppe; Panak, Petra; Roesky, Peter W. (Inorganic chemistry, 2024)
Here, we report the synthesis of the 6-(6-methyl-1,2,4,5-tetrazine-3-yl)-2,2′-bipyridine (MTB) ligand that has been developed for lanthanide/actinide separation. A multimethod study of the complexation of MTB with trivalent actinide and lanthanide ions is presented. Single-crystal X-ray diffraction measurements reveal the formation of [Ce(MTB)2(NO3)3], [Pr(MTB)(NO3)3H2O], and [Ln(MTB)(NO3)3MeCN] (Ln = Nd, Sm, Eu, Gd). In addition, the complexation of Cm(III) with MTB in solution was studied by time-resolved laser fluorescence spectroscopy. The results show the formation of [Cm(MTB)1-3]3+ complexes, which occur in two different isomers. Quantum chemical calculations reveal an energy difference between these isomers of 12 kJ mol-1, clarifying the initial observations made by time-resolved laser fluorescence spectroscopy (TRLFS). Furthermore, quantum theory of atoms in molecules (QTAIM) analysis of the Cm(III) and Ln(III) complexes was performed, indicating a stronger covalent contribution in the Cm-N interaction compared to the respective Ln-N interaction. These findings align well with extraction data showing a preferred extraction of Am and Cm over lanthanides (e.g., max. SFAm/Eu = 8.3) at nitric acid concentrations <0.1 mol L-1 HNO3.
Veröffentlicht: 5. August 2024
Gesehen am 12.05.2025